Effect of age, gender and formal education on endogenous knowledge of woody plants in communities bordering forest patches of the Lubero Mountain Massif (DR Congo) - Ndavaro, Norbert K.; Hegbe, Apollon D.M.T.; Dramani, Ramdan; Dicko, Aliou; Sahani, Muhindo W.; Natta, Armand K (Ethnobotany Research and Applications, 2024)
Background: In rural human societies, people’s knowledge of plants can vary according to some factors, including socio-demographic characteristics. This study was carried out among local communities living near forest patches of the Lubero Mountain Massif in north-eastern Democratic Republic of Congo (DR Congo). Its aim was to assess the effect of age, gender and formal education on the level of endogenous knowledge of woody plants of the forest patches. Methods: Ethnobotanical surveys were carried out among 449 people in 13 villages bordering forest patches in the study area, using semi-structured individual interviews and focus groups. The different categories of use of woody plants were identified. The effect of age, gender and formal education on the level of local knowledge of woody plants was investigated using negative binomial regression. Results: A total of 80 woody species belonging to 77 genera and 43 families were mentioned by the respondents, who used them in five main categories: energy, handicrafts, medicine, construction and food. Age and gender had a significant effect on the number of woody species identified (P<0.05). Old people (age ≥ 60 years) knew on average twice as many woody species as adults (30 < age < 60) and young people (age ≤ 30 years), while men knew significantly more species than women. Conclusions: These findings confirm the unequal distribution of endogenous knowledge based on socio-demographic factors and suggests that males and older people with more knowledge of woody species should be considered as key players in the conservation of woody plant resources in the study area. Keywords: Ethnobotanical hypothesis, Endogenous knowledge, Socio-demographic characteristics, Woody plants, Conservation, Mountain forests, Lubero, DR Congo.